Potencijal bakterija za proizvodnju bioetanola iz lignoceluloznih sirovina - Petravić, Vlatka; Tolvajčić, Martina; Stanzer, Damir; Mrvčić, Jasna; Hanousek-Čiča, Karla; Šantek, Božidar (2018)
Poljoprivreda, šumarstvo i prehrambena industrija izvori su velike količine lignocelulozne biomase, koja može poslužiti kao lako dostupna i jeftina obnovljiva sirovina za dobivanje različitih bioproizvoda. Jedan od takvih proizvoda je i bioetanol. Ovaj rad daje pregled bakterija koje se koriste i/ili istražuju za proizvodnju bioetanola iz lignoceluloznih sirovina. U navedenim istraživanjima proizvodnje bioetanola pomoću bakterija primijenjuju se različiti pristupi kako bi se povećala ekološka i ekonomska efikasnost procesa. Pored uobičajenih bioprocesa, koji se provode u više faza i uz pomoć monokulture, razvijaju se i visokointegrirani (konsolidirani) bioprocesi uz primjenu mikrobnih kokultura.
Agriculture, forestry and food industry are sources of large quantities of lignocellulosic biomass, which can be used as an easily accessible and cheap renewable raw material for production of different bioproducts. One of these bioproducts is also bioethanol. This paper provides an overview of bacteria used and/or investigated for bioethanol production from lignocellulose-containing feedstocks. In the research of bioethanol production using bacteria, various approaches are applied in order to increase ecological and economic efficiency of bioprocess. In addition to conventional multi-stage bioprocesses that are carried out using monoculture, highly integrated (consolidated) bioprocesses and applications of microbial cocultures are also in developing stage.
Bibliografija: str. 80-82.
Sažetak ; Abstract.
Keywords: Bioetanol -- Lignoceluloza -- Bakterije -- Heksoze -- Pentoze -- Inhibitori